Peran Pondok Pesantren Darul Ulum Talaga Ganding dalam Pemberdayaan Ekonomi Perempuan - Kusik Kusuma Bangsa (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2022)
This research aims to determine the economic empowerment program strategy by PP. Darul Ulum Talaga Ganding and the impacts of this program on the economic independence of the society, especially women community. The method used in this research is qualitative descriptive and phenomenological with data collection in the form of observation, interviews and documentation. The theory used in this research is people centered development theory. The research shows that the PP. Darul Ulums model of economic empowerment is carried out in three ways: carrying out sewing training for women in Talaga Village, establishing a savings and loan cooperative for small business capital and agricultural capital, and managing a women's farmer group called KWT Suka Maju. The implications of these three programs are that women have businesses that generate money to help the household economy and do not just rely on the income of their husbands who have migrated. Because the women had additional income, their sons started to go to school. Many young men are interested in working on rented rice fields rather than leaving their wives and children.